Effects of Treadmill Exercise on Hippocampal Synaptic Plasticity and Expression of Related Proteins in Aging Mice - WANG Sinuo; CAO Yajun; XIANG Qing; YAN Jiamin; LIN Yanting; ZHUANG Yueyang; GUO Xiaoqin; LIU Weilin (康复学报)
ObjectiveTo explore the role and possible mechanism of cognitive function-related factors and BDNF/TrkB/PI3K signaling pathway in the treadmill exercise intervention with the decline of cognitive memory function in naturally aging mice.MethodsA total of 16 months old C57BL/6J mice were randomly divided into the aged group and the exercise group, through a random number table method, with 8 mice in each group. And 6-month-old mice of the same strain were taken as the adult group (n=8). The exercise group performed a 6-week treadmill exercise, 1 hour each time, once a day, and 5 days a week, for 6 weeks. The baseline memory function was detected by Morris water maze test before intervention. The memory function of mice in each group after intervention was detected by Barnes maze test, T maze test and new object recognition test. Nissl staining was used to detect the morphology of hippocampal neurons, Golgi staining was used to detect the number of dendritic spines in the hippocampus. RT-PCR was used to detect the changes of cognitive function-related factors in the hippocampus of aged mice, and Western blot was used to detect the changes of BDNF/TrkB/PI3K signaling pathway related proteins in the hippocampus.ResultsThe escape latency time of Barnes maze in the aged group was significantly longer than that in the adult group (P<0.05), and the spontaneous alternation rate of T maze and the recognition rate of new objects significantly decreased (P<0.05). However, after treadmill exercise, the escape latency time of Barnes maze in the exercise group was significantly shorter than that in the aged group (P<0.05), and the spontaneous alternation rate of T maze and the recognition rate of new objects increased (P<0.05). Compared with the adult group, the hippocampal neurons in the aged group were lightly stained, the number reduced, the arrangement was sparse; compared with the aged group, the exercise group showed darker staining, arranged in order, and more in quantity. Compared with the adult group, the density of hippocampal dendritic spines in the aged group significantly decreased (P<0.05), while the density of hippocampal dendritic spines in the exercise group increased than that of the aged group (P<0.05). The results of RT-PCR showed that the expression of Dlgap2, GNG4 and KCNQ2 mRNA in the hippocampus of mice in the aged group was lower than that in the adult group, and the expression of GNG4 and KCNQ2 mRNA significantly decreased (P<0.05), while the expression of Dlgap2, GNG4 and KCNQ2 mRNA in the hippocampus of mice in the exercise group increased, and the expression of GNG4 mRNA significantly increased than that of the aged group (P<0.05). In addition, the protein contents of BDNF, TrkB, CREB, PI3K and Akt in the hippocampus of the aged group were significantly lower than those of the adult group (P<0.05), while the protein contents of BDNF, TrkB in the hippocampus of the exercise group were higher than those of the aged group (P<0.05).ConclusionThe 6-week treadmill exercise can improve the cognitive memory function of aging mice. The possible mechanism is to increase the expression of cognitive function-related factors in the hippocampus of aging mice by activating the BDNF/TrkB/PI3K signaling pathway, reduce hippocampal nerve damage, and enhance synaptic plasticity, thereby improving memory function.